Spelling Errors in the Comment Column and Status of Sanggar Mahera Instagram Social Media Post - Inzaghi, Nofiko Azalea; Arifin, Zainal (Universitas Muhammadiyah Surakarta, 2023)
This study aims to analyze language errors in the comments and status of Sanggar Mahera's posts. This type of research is descriptive qualitative research. The object of research in this study is the comment column and the status of Instagram posts that experience language errors. The data in this study used qualitative data, namely data collected in the form of words and sentences that were language errors. The data collection technique used in this study is the observation and note-taking technique. Data analysis used a qualitative descriptive method. The results obtained in the analysis of language errors in the comments and status of Sanggar Mehara's posts found that there were errors in the use of spelling that were still not quite right. The results obtained from the analysis of language errors in the comments and status of Sanggar Mihara posts found errors in the use of spelling that were still inaccurate, such as errors also found in the status of posts written by the owner of the Sanggar Mahera account.